CONSISTENCY OF THE IMPLEMENTATION OF RULES AND PROCEDURES AS AN EFFORT TO DEVELOP STUDENT DISCIPLINE FOR GRADE 1 - Priska Pebrianti Liu; Wiyun Philipus Tangkin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The discipline in learning is crucial to achieving the effectiveness of teaching-learning. In fact, it is still found that there are undisciplined students encountered during the learning process. Based on the observation results of elementary school students at one of the Christian schools, students who did not follow the rules and procedures were found, such as not using a raised hand so which causes the class to be conducive or unstable. The solution to this problem is the consistency of rule and procedure implementation. It is aimed to see the consistency of the rule and procedure implementation as an attempt to develop the first-grade students’ discipline. The method used is a descriptive qualitative method. The result indicates the consistency of the rule and procedure implementation can develop students’ discipline. It is characterized by an attitude change indicated by students. Still, teachers’ consistency is needed continually in order to make significant behavior. As Christian educators, teachers certainly must believe in the truth of God as a source as the bible, see the existence of God through Jesus Christ as an exemplar, and reflect good character, but must realize that only the holy spirit can empower every student. The recommendation that can be given to teachers is that teachers must be consistent in applying each class rule and procedure so it can produce a significant change in attitude.